The Policy on Tourism MSMEs in Indonesia and Algeria: Sustainability and Challenges - Hasanah, Uswatun; Driss, Bakhouya (Journal of Human Rights, Culture and Legal System, 2023)
Tourism legislation should encourage tourism MSMEs; otherwise, these enterprises are likely to remain local or go unnoticed globally. This study aims to investigate the emerging urgency arising from the interrelationship between MSMEs' legal policies and tourism legislation. This research belongs to normative research conducted by employing statutory and comparative approaches. The study reveals that adopting social capital as the foundation of tourism legislation enhances the role of tourism MSMEs in economic development. Furthermore, the legal policies enacted for running tourism businesses based on social capital seem to provide legal certainty for protecting and empowering tourism MSMEs and boosting their global competitiveness.